HYBRID YOUNG-MUSLIM: Intersection Manhaj, Political Identity, and Modernity through Social Media - Muhammad Iqbal Juliansyahzen (Ijtimā iyya Journal of Muslim Society Research, 2021)
This article analyzes the religious phenomenon of young Muslims who are channeled through social media. Along with the swift currents of modernization, digitalization, and globalization, it is possible to cross subcultures in the dynamics of human life, including in religious matters. On the one hand, in the religious context, there are specific guidelines (manhaj), but on the other hand, they want to maintain their identity as young people. The results of the struggle and synthesis of various elements gave birth to a form of religion called Hybrid Muslim. Forms of religion can be seen from the model of dress and social relations. The influence of religious groups in the construction of Muslim religion in the media is very large. They use a number of strategies to spread their religious understanding so that it fits the character of young Muslims. The manhaj most influential in the construction of Muslim religiosity is manhaj the conservative religious. Nevertheless, young people's religious identity is not eliminated, namely millennial, modern, and Islami.